Incidence of hypernatremia in dogs treated with single dose activated charcoal for acute toxicant ingestion: multi-center retrospective study (2018–2023) - Young, Timothy; Walton, Rebecca A. L.; Cheng, Poyee; Cai, Jiazhang; Mochel, Jonathan P.; Peterson, Katherine (Frontiers in Veterinary Science, 2025)
ObjectiveTo retrospectively evaluate the incidence and clinical significance of hypernatremia in dogs administered a single dose of activated charcoal (AC) or activated charcoal with sorbitol (ACS) for acute toxicant ingestion.MethodsRetrospective study between the years 2018–2023. Ninety-six dogs evaluated by a university teaching hospital and private practice emergency hospital treated for acute toxicant ingestion with a single dose of activated charcoal, with or without sorbitol.ResultsMedical records were retrospectively reviewed. No dog developed hypernatremia, defined as sodium >155 mEq/L, during the study period. The toxicant ingested was not significantly associated with a change in sodium (Na) at any time point (P = 0.433 at 6–12 h, P = 0.09 at 12–14 h, and P = 0.486 at 24–48 h). Ingestion of multiple toxicants, compared to single toxicant ingestion, was also not significantly associated with a change in Na at any time point (P = 0.126 at P = 6–12 h, P = 0.452 at 12–24 h, and P = 0.516 at 24–48 h). Time from ingestion to presentation was not significantly associated with a change in Na at any time point (P = 0.422 at 6–12 h, P = 0.881 at 12–24 h, and P = 0.516 at 24–48 h). The administration of AC compared to ACS was not significantly associated with a change in Na at any time period (P = 0.715 at 6–12 h, P = 0.137 at 12–24 h, P = 0.582 at 24–48 h). There was a significant difference between Na on presentation and at 12–24 h and 24–48 h (P = 0.025 and P = 0.015, respectively.) Median Na values decreased at all-time points when compared to presentation, −0.90 at 6–12 h (standard deviation (SD) 2.74), −1.38 at 12–24 h (SD 4.81) and −2.11 at 24–48 h (SD 5.34).ConclusionsThis study demonstrated a statistically significant, but unlikely clinically significant, decrease in Na in dogs who received single dose AC or ACS for acute toxicant ingestion.